Peningkatan Kemampuan Motorik Kasar Anak Usia Dini Melalui Bermain Lempar Tangkap Bola - Djuanda, Isep; Adipura, Putri (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2020)
This study aimed to find out the implementation of a throw-and-catch ball game on young learners aged 5-6 years old in PAUD Nurul Fadillah and discovered young learners’ hard motoric skill improvement through the game.Conducted as a Class Action Research, this study involved 11 young learners as the subject as well as object of the study. The study process was carried on by applying two cycles, 1 and 2, which was initiated by a pre-cycle activity. There were four steps taken in each cycle which included planning, doing, observing, and reflecting. The data collection was obtained by observation, interview, and documentation study.The result of the study showed that: 1) The implementation of a throw-and-catch ball game had resulted in the improvement of hard motoric skill on young learners aged 5-6 years old in PAUD Nurul Fadillah on these categories: 82% on balancing, 91% on power and flexibility; 2) The implementation of playing a throw-and-catch ball game was able to improve hard motoric skill on young learners aged 5-6 years old in PAUD Nurul Fadillah Depok, since they have succeeded in achieving the predefined success indicators on balance, power and flexibility.